Edukasi dan Pemeriksaan Dini Apolipoprotein untuk Menurunkan Risiko Penyakit Kardiovaskular di Masyarakat - Charissa, Olivia; Santoso, Alexander Halim; Wijaya, Bryan Anna; Rafi, Muhammad Adam Abizar; Pratama, Muhammad Kevin Dava (PT. Riset Press International, 2026)
Cardiovascular disease remains the leading cause of global mortality, with a growing burden particularly in low- and middle-income countries, including Indonesia. Atherogenic dyslipidemia—marked by an imbalance between apolipoproteins, specifically elevated Apolipoprotein B and reduced Apolipoprotein A—has emerged as a more accurate cardiometabolic risk indicator than conventional lipid measurements. This community service program aimed to enhance early detection and health education regarding apolipoprotein profiles among the elderly population in South Jakarta. A total of 99 participants (mean age 71.85 years; 71.7% female) underwent ApoA and ApoB testing and received targeted health education. Results showed that 16.2% of participants had elevated ApoB levels, while all participants (100%) exhibited ApoA levels within the high-risk category. Based on the ApoB/ApoA ratio, 25.3% of participants were classified as having high cardiovascular risk. These findings highlight the need to integrate apolipoprotein-based screening into primary healthcare services, supported by educational interventions focusing on lifestyle modification, to help reduce the community burden of cardiovascular disease.